Synergistic power of functional foods and exercise in colorectal cancer control: targeting metabolism, mitochondrial function, redox homeostasis, exercise performance, neuroimmune signaling, and brain–gut axis crosstalk - Cheng, Mengliang; Li, Yunlong; Liang, Danqing; Wu, Chuanzhong (Frontiers in Nutrition, 2025)
Gastrointestinal (GI) cancers—including colorectal, gastric, esophageal, and pancreatic malignancies—are among the most prevalent and lethal cancers globally. Despite advancements in treatment, the prognosis for many patients remains poor, highlighting the urgent need for integrative and preventive approaches. Functional foods, rich in bioactive compounds such as polyphenols, flavonoids, carotenoids, and omega-3 fatty acids, possess potent antioxidant, anti-inflammatory, and antitumor properties. Meanwhile, exercise has emerged as a non-pharmacological intervention capable of modulating systemic inflammation, enhancing immune responses, and improving quality of life in cancer patients. This review critically examines the synergistic impact of consuming functional foods and engaging in regular physical activity on the molecular pathways underlying the initiation and progression of GI cancer. Emphasis is placed on key signaling cascades, which are implicated in oxidative stress, inflammation, cell proliferation, apoptosis, and metastasis. Furthermore, the role of neurotrophic factors—particularly brain-derived neurotrophic factor—is explored, revealing their potential as molecular links between gut–brain axis modulation, cancer pathophysiology, and exercise-induced neuroprotection. By integrating current preclinical and clinical evidence, this review highlights the potential of combining functional nutrition with exercise as a holistic, personalized strategy for preventing and managing GI cancers. Such approaches may not only target tumor biology but also improve cognitive function, mood, and overall patient wellbeing, paving the way for precision lifestyle medicine in oncology.